Experiences of being diagnosed with motor neuron disease: "I just want to know". Issue 5 (October 2019) - Remm, Sarah; Halcomb, Elizabeth; Stephens, Moira
Abstract: Background: The diagnosis of a life limiting condition such as motor neurone disease (MND) is a challenging process for all affected by it. There is little research exploring the experience of living with MND. Understanding people's experiences of a diagnosis of MND can help improve diagnosis experiences and relationships with health professionals. Aim: This paper reports on a study exploring the diagnosis experiences of people living with MND, and how these experiences have impacted their lives. Methods: A qualitative descriptive approach was used. Semi-structured interviews were undertaken with six participants diagnosed with MND. Interviews were transcribed verbatim and analysed using thematic analysis. Findings: Four themes emerged, namely Barriers to early diagnosis increase uncertainty ; Being treated like a person ; Regaining self and control of life; and Support. The results support the need for timely diagnosis to reduce uncertainty and increase trust and interaction with health professionals. Findings also emphasise the importance of early referral to support services and provision of disease specific resources to augment the input of health professionals. Conclusion: The diagnosis period is a crucial and sensitive time for people with MND. These findings highlight how understanding the experiences of those being diagnosed with MND can guide health professionals in their management of the diagnosis process. Improved outcomes for patients may be achieved through enhancing the diagnosis experience.